Superior sagittal sinus thrombosis in a case of beta thalassaemia major - Azad, Syed Md; Mukherjee, Anwesha; Kapoor, Rohit; Bannerji, Rohit; Ray, Jaydeb (International Journal of Advances in Medicine, 2017)
Patients with beta- thalassaemia major have a wide spectrum of clinical manifestations, from transfusion dependency to asymptomatic anaemia. Some may just have incidental finding of anaemia with splenomegaly during physical examination. Most of them require regular blood transfusion and their haemoglobin is maintained at an acceptable level. However they are at risk for multiple complications such as thrombo-embolic events which may be life threatening. We report here a case of beta- thalassaemia major complicated by cerebral sinus thrombosis, who had minimal clinical symptoms and signs at presentation. This case reiterates the importance of increased vigilance in the clinical management of this vulnerable group of patients.